Metformin suppresses pregnane X receptor (PXR)-regulated transactivation of CYP3A4 gene - Krausova, Lucie; Stejskalova, Lucie; Wang, Hongwei; Vrzal, Radim; Dvorak, Zdenek; Mani, Sridhar; Pavek, Petr (Biochemical pharmacology, 2011)
Metformin is widely used in the treatment of type-2 diabetes. The pleotropic effects of metformin on glucose and lipid metabolism have been proposed to be mediated by the activation of AMP-activated protein kinase (AMPK) and the subsequent up-regulation of small heterodimer partner (SHP). SHP suppresses the functions of several nuclear receptors involved in the regulation of hepatic metabolism, including pregnane X receptor (PXR), which is referred to as a "master regulator" of drug/xenobiotic metabolism. In this study, we hypothesize that metformin suppresses the expression of CYP3A4, a main detoxification enzyme and a target gene of PXR, due to SHP up-regulation. We employed various gene reporter assays in cell lines and qRT-PCR in human hepatocytes and in Pxr(-/-) mice. We show that metformin dramatically suppresses PXR-mediated expression of CYP3A4 in hepatocytes. Consistently, metformin significantly suppressed the up-regulation of Cyp3a11 mRNA in the liver and intestine of wild-type mice, but not in Pxr(-/-) mice. A mechanistic investigation of the phenomenon showed that metformin does not significantly up-regulate SHP in human hepatocytes. We further demonstrate that AMPK activation is not involved in this process. We show that metformin disrupts PXR's interaction with steroid receptor coactivator-1 (SRC1) in a two-hybrid assay independently of the PXR ligand binding pocket. Metformin also inhibited vitamin D receptor-, glucocorticoid receptor- and constitutive androstane receptor (CAR)-mediated induction of CYP3A4 mRNA in human hepatocytes. We show, therefore, a suppressive effect of metformin on PXR and other ligand-activated nuclear receptors in transactivation of the main detoxification enzyme CYP3A4 in human hepatocytes.
Keywords: polohový reflex; Cells, Cultured; lidé; koaktivátory jaderných receptorů; proteinkinasy aktivované AMP; receptory kalcitriolu; Mice, Knockout; metformin; Reflex, Righting; hepatocyty; pregnanový X receptor; aktivace transkripce; Cytochrome P-450 CYP3A; Pregnane X Receptor; receptory glukokortikoidů; Genes, Reporter; messenger RNA; RNA, Messenger; Signal Transduction; kultivované buňky; myši; AMP-Activated Protein Kinases; Hepatocytes; Humans; Nuclear Receptor Coactivators; Mice; reportérové geny; Receptors, Cytoplasmic and Nuclear; signální transdukce; Metformin; Receptors, Calcitriol; Transcriptional Activation; cytochrom P-450 CYP3A; membránové proteiny; zvířata; receptory cytoplazmatické a nukleární; Mice, Inbred C57BL; Membrane Proteins; steroidní receptory; Animals; myši knockoutované; Receptors, Glucocorticoid; Receptors, Steroid; hypoglykemika; Hypoglycemic Agents; konstitutivní androstanový receptor; myši inbrední C57BL; Constitutive Androstane Receptor